Iowa Birdline update, January 21, 1991 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Email of the Iowa Birdline update for January 21, 1991. Highlights include multiple Snowy Owl reports. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed